Analisis Terhadap Misi Peacebuilding United Nations Transition Administration in East Timor (Untaet) - Sugito, Sugito (Universitas Muhammadiyah Yogyakarta, 2013)
This research aims to determine how UNTAET implemented the mandate as an institution of peace in East Timor, what challenges must be faced in running the mandate. This research based on the literature study methods by using data from journals, books, and sources from the internet. This research shows that UNTAET is success to run the mandate as the institution of peace, especially in the development of security institutions (police, army, judiciary), in the economic (monetary and fiscal), in the politics (government and general election) also in handling humanitarian issues. However, this research also indicates the emergence of some obstacles in implementing UNTAET programs, such as UNTAET institution tends to authoritarian, the lack of local staff in understanding the culture of Timor society, also the lack of support from the International Community. In addition, other challenges come from the lack of Timor society participation in supporting program which designed by UNTAET, also political institution problems and security of former members of Falintil.